One-day low-residue diet is equally effective as the multiple-day low-residue diet in achieving adequate bowel cleansing: a meta-analysis of randomized controlled trials - Raeni Dwi Putri; Fiki Amalia; Festy Aldina Utami; Yunisa Pamela; Mas Rizky A.A. Syamsunarno (Clinical Endoscopy)
Background/Aims Colonoscopy is widely used as a diagnostic and preventive procedure for colorectal diseases. The most recent guidelines advocate the use of a low-residue diet (LRD) for bowel preparation before colonoscopy. LRD duration varies considerably, with recommended 1-day and multiple-day regimens in clinical practice. Methods We followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. We searched multiple databases for randomized controlled trials (RCTs) and analyzed the outcomes using a fixed-effects model. Results Six RCTs with 2,469 subjects were included in this study. The rates of adequate bowel preparation for 1-day and >1-day were 87.2% and 87.1%, respectively. No statistically significant differences were observed between the 1-day and >1-day LRD in adequate bowel preparation (odds ratio [OR], 1.03; 95% confidence interval [CI], 0.76–1.41; p=0.84; I2=0%), polyp detection rate (OR, 0.91; 95% CI, 0.76–1.09; p=0.29; I2=16%), adenoma detection rate (OR, 0.87; 95% CI, 0.71–1.08; p=0.21; I2=0%), and withdrawal time (mean difference, –0.01; 95% CI, –0.25 to 0.24; p=0.97; I2=63%). Conclusions The efficacy of 1-day and multiple-day LRD is comparable in achieving satisfactory bowel preparation, highlighting their similar impact on the detection of polyps and adenomas during colonoscopy.